POSITION OF ELECTRONIC EVIDENCE IN THE PROCESS OF PROVIDING PROCEDURE IN STATE ADMINISTRATIVE COURT The Position of Electronic Evidence in the Evidentiary Process of State Administrative Court Procedural Law - Komang Alit Antara; Moh. Fadli; Sudarsono (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study analyzes the position of electronic evidence in the legal evidence process of the State Administrative Court. The development of information technology has had significant implications for the justice system, especially in the recognition and use of electronic evidence. However, there is a gap between the increasingly digitalized practice of government administration and the PTUN procedural law mechanism which still focuses on physical documents. This study uses normative legal analysis conducted with a statutory and conceptual regulatory approach, using data from related laws and legal literature. The results of the study indicate that the unclear regulations in Law Number 5 of 1986 concerning the PTUN, although the ITE Law has recognized electronic evidence, cause legal uncertainty, differences in judge interpretation, and potential manipulation of evidence. Therefore, this study recommends the reconstruction of PTUN procedural law norms to include explicit provisions regarding electronic evidence, the establishment of a digital forensic validation institution, and the regulation of authentication and security of electronic documents. These steps are important to ensure justice, legal certainty, and efficiency in resolving state administrative disputes in the digital era.